Haikyu!! / vol. 1 - Furudate, Haruichi, 1983-; Beck, Adrienne; Terriquez, Erika, 1984-; Lau, Fawn; First, Marlene (2016)
"Ever since he saw the legendary player known as 'the Little Giant' compete at the national volleyball finals, Shoyo Hinata has been aiming to be the best volleyball player ever! Who says you need to be tall to play volleyball when you can jump higher than anyone else? After losing his first and last volleyball match against Tobio Kageyama, 'the King of the Court, ' Shoyo Hinata swears to become his rival after graduating middle school. But what happens when the guy he wants to defeat ends up being his teammate?!"--
v. 1. Hinata and Kageyama --
"Reads from right to left"--Last page.
"First published in Japan in 2012 by SHUEISHA Inc., Tokoyo"--Title page verso.
Translated fom the Japanese.
Keywords: COMICS & GRAPHIC NOVELS -- Manga -- Media Tie-In.; COMICS & GRAPHIC NOVELS -- Manga -- Sports; Comic books, strips, etc; Volleyball; Japan; Comic books, strips, etc; Comics (Graphic works); Graphic novels; Translations; Graphic novels